EVALUATION OF ABUTMENT TEETH IN FIXED PARTIAL DENTURE- A RETROSPECTIVE ANALYSIS OF THE PATIENT RECORDS - Karpagam, G. Nithya; Ramanathan, Visalakshi; Prabu, Dinesh (International Journal of Psychosocial Rehabilitation, 2019)
The aim of this study is to evaluate the abutment teeth selection in fixed partial denture (FPD) done by undergraduate students.For this, patient records of those who underwent replacement of missing teeth with fixed partial denture were collected. A total of 50 patient radiographs were evaluated. The data on the following parameters: gender and age of the patient, crown root ratio, pocket depth, mobility, axial alignment of the abutment tooth, existing caries and periapical lesion or pulpal involvement and alveolar ridge form were collected. The data was tabulated in excel sheet. After data collection descriptive statistical analysis was done in SPSS software. In the current study the most prevalent gender in the study population to undergo FPD treatment were males (66%) than females (34%). The most prevalent age group opting for FPD treatment was between 41-50 years(52%). 38% of the evaluated FPD abutments had a Crown root ratio of 1:1, 40% of the abutments chosen for FPD construction were detected to have caries. Periapical lesion was present in 13% of the abutment teeth evaluated. Axial alignment of the tooth showed mostly normal alignment representing (65%); pulpal involvement and root canal treatment were done in 17% of the evaluated abutments. The alveolar ridge form of the evaluated patients showed flat ridge (58%). The present study shows appropriate parameters that have to be evaluated by undergraduate students during abutment selection for treatment planning of FPD.